Is Uncertainty about Future Earnings Higher for Emerging Economy Enterprises? - Kang, Tony (Institutional Knowledge at Singapore Management University, 2003)
Anecdotal evidence suggests that emerging economy enterprises face higher uncertainty in business operations compared to their counterparts in more developed economies. However, there is little empirical evidence on this issue. The objective of this study is to fill this void in the literature and examine whether there is an association between the level of development of home country economy of a multinational corporation and uncertainty about future earnings measured by dispersion in analysts' earnings forecasts. After controlling for various firm- and country-level factors, I find that the forecast dispersion tends to be larger for emerging economy enterprises (i.e., non-U.S. firms cross-listed in the U.S. whose home country economy is better characterized as emerging) than for developed economy enterprises (i.e., non-U.S. firms cross-listed in the U.S. whose home country economy is better characterized as developed), despite the fact that the emerging economy enterprises tend to be more heavily followed by analysts. Overall, the evidence supports the view that business uncertainty tends to be higher in emerging economies and highlights inherent difficulties associated with predicting future firm performance of the emerging economy enterprises.